CFD-DPM Numerical Investigation of Erosion-Corrosion in Elbow 180° Evaporator Tube HRSG: Effect of Weld Defect and Feedwater TDS on Flow-Accelerated Corrosion - Ricky Rahmadani; Harus Laksana Guntur (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Heat Recovery Steam Generator (HRSG) evaporator tubes are susceptible to premature failure due to the combined effects of flow-accelerated corrosion (FAC) and erosion under high-temperature two-phase flow conditions. Understanding the interaction between hydrodynamic behavior, weld defects, and feedwater quality is essential for improving HRSG reliability. This study aims to investigate the effect of weld defects and feedwater total dissolved solids (TDS) on erosion-corrosion behavior in a 180° evaporator tube elbow of an HRSG system. A numerical case study was conducted using Computational Fluid Dynamics coupled with the Discrete Phase Model (CFD-DPM) implemented in ANSYS Fluent. Two tube configurations, namely a weld-defective tube and a defect-free tube, were simulated under actual operating conditions, while TDS concentration was represented by discrete solid particles. The results indicate that the 180° elbow geometry generates high turbulence and particle impingement, leading to localized erosion at the downstream outer curvature of the elbow. Under actual operating conditions with an average feedwater TDS of 1,873 ppm, the predicted erosion rate reached 1.83 mm/year in the weld-defective condition, compared with 0.55 mm/year in the defect-free condition, indicating more than a threefold increase in material degradation. Higher TDS levels further accelerated the erosion process. The predicted erosion hotspot corresponded closely with the actual leakage location observed in the field. These findings demonstrate that the synergistic interaction of FAC, particle-induced erosion, elevated TDS, and weld defects is the primary cause of repeated evaporator tube failures in the investigated HRSG system.